2016
DOI: 10.1007/s11136-016-1371-x
|View full text |Cite
|
Sign up to set email alerts
|

HRQoL impact of stressful life events in children beginning primary school: results of a prospective study in Poland

Abstract: PurposeTo evaluate the relationship between recent stressful life events (SLEs), stress-related symptoms (SRSs), and health-related quality of life (HRQoL) in children beginning primary school.MethodsA community-based sample of 6- to 8-year-old children (176 boys and 175 girls at baseline) participated in a prospective longitudinal study with three waves of data collection and 1-year interval between subsequent surveys, conducted in the Wielkopolska Province, Poland. Main exposures included nine recent stressf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The allostatic load model [16] can explain how cumulative stress negatively impact the body as multiple physiological systems are strained over time caused by repeated mobilizations in response to stress exposure [17,18]. More frequent and persistent exposures accelerate this impact, regardless of what specific events occur [8]. However, this has primarily been examined in young adolescents [6,8,19].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The allostatic load model [16] can explain how cumulative stress negatively impact the body as multiple physiological systems are strained over time caused by repeated mobilizations in response to stress exposure [17,18]. More frequent and persistent exposures accelerate this impact, regardless of what specific events occur [8]. However, this has primarily been examined in young adolescents [6,8,19].…”
mentioning
confidence: 99%
“…More frequent and persistent exposures accelerate this impact, regardless of what specific events occur [8]. However, this has primarily been examined in young adolescents [6,8,19]. Although FRSLEs are linked to reduced health when examined concurrently in preadolescence [6], it is unknown whether this relationship persists through adolescence and whether exposure earlier is associated with negative health outcomes later in adolescence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, research has shown the correlation of ACEs with health outcomes within Eastern Europe and Poland; however, current studies of ACEs in Poland consist of retrospective ACE screening of adults. One prospective longitudinal study of 6-8-year-old children in Poland (N = 291) revealed an association between recent stressful lifeful events, symptoms related to stress, and negative impacts on a health-related quality of life survey [5]. While this further supports the importance of stressful events on paediatric health, this study focused on recent stressful events and shorter health quality outcomes.…”
Section: Introductionmentioning
confidence: 74%
“…The lack of Polish language versions of HRQoL questionnaires addressed to children and adolescents, with good psychometric characteristics is even more distinct. Since there is a growing number of studies on health-related quality of life in Polish children (e.g., Dyga-Konarska and Bieganowska 2004;Bączyk 2008;Magiera et al 2017;Mathiak et al 2007;Kaczmarek and Trambacz 2016;Brzycki et al 2019), it is very important to increase availability of Polish versions of questionnaires suitable for measuring children's and youths' HRQoL in general population and patients as well.…”
Section: Introductionmentioning
confidence: 99%